PKM Gathering Otomatisasi Tata Kelola Perkantoran Pada SMK Negeri 1 Kota Bogor - Listari, Sinta (Jurnal Abdimas Dedikasi Kesatuan, 2024)
The Student Creativity Program (PKM) themed "Gathering on Office Administration Automation (OTKP)" at SMK N 1 Kota Bogor aims to enhance students' skills and knowledge in automated office administration. This activity is designed to provide practical understanding of the use of technology in office management, which includes digital document management, automation of administrative tasks, and the implementation of information management systems. The methods used in this PKM include workshops, simulations, and group discussions, allowing students to learn interactively and applicatively. The results of this activity showed a significant increase in students' understanding of OTKP concepts and applications, as well as their ability to implement technology to improve the efficiency and effectiveness of administrative work. This activity is expected to prepare SMK N 1 Kota Bogor students to enter the workforce with relevant and competitive skills in the digital era.   Keywords: Office Management, improving skills